A new experimental method for measuring stress-temperature phase diagram in shape memory alloys. (September 2018) - Bronstein, Emil; Faran, Eilon; Shilo, Doron
Abstract: The martensitic phase transformation in shape memory alloys (SMA) can be described by stress-temperature phase diagram, which provides fundamental scientific and applications-related information on this important process. We present a new experimental method that enables direct measurement of the complete stress-temperature phase diagram of SMA within a single experiment. The experimental setup is placed under an optical microscope and allows complementary visualization of the microstructure evolution throughout the phase transformation. The method is demonstrated on a SMA Ni-Mn-Ga single crystal, and the values of the Clausius-Clapeyron relation along with the latent heat of the transformation are extracted. Graphical abstract: Unlabelled Image